Financial intermediation in deposit money banks and Nigerian economy - Adeyinka, Adewole Joseph; Akanmu, Popoola Mufutau; Innocent, Idachaba Odekina (The Journal of V. N. Karazin Kharkiv National University. Series: International Relations. Economics. Country Studies. Tourism, 2020)
The paper summarizes the arguments and counterarguments within the scientific discussion on financial intermediation in deposit money banks and economic growth in Nigeria. The main purpose of the research is to examine the relationship between financial intermediation in deposit money banks and the Nigerian economy. A systematization literary approach for solving the problem is Regression Analysis. Secondary data was sourced from Central Bank of Nigeria Statistical Bulletin. The results of findings within the years of analysis (2000-2017) indicated that there was significant relationship between Total Bank Credit and monetary policy indices on deposit money banks in Nigeria. It was also discovered that there was significant relationship between Gross domestic product and total credit in deposit money banks of Nigeria. Based on the objective and findings of this study, the study therefore recommends that Deposit Money Banks in Nigeria should foster higher level of liquidity in order to increase its ability to cover withdrawals made by its customers and to increase the loan and advances to customers even with the monetary policy indices on deposit money banks. The study also recommends that Deposit Money banks should distribute adequate credit to the real sector for productive purposes in order to increase Gross domestic product. The conclusions that can be drawn from the findings of this study is that with the level of minimum reserve maintained by Deposit Money bank with Central bank of Nigeria, there is adequate availability of credit for real sector investments. High lending rates of deposit money banks may make many customers/investors to consider other sources of finance. Bank Credit/loan is still greatly increasing the production of goods and services in the Nigeria Deposit Money Banking System because of utilisation of the loans by investors.